Goal perspectives and motivational responses elite junior weightlifters - Fry, M. D.; Fry, A. C. (The Journal of Strength and Conditioning Research, 1999)
The purpose of this study was to use a theory of achievement motivation to examine the goal perspectives and motivational responses of elite junior athletes. Participants (N = 171; 48 females and 123 males; mean age = 15.0 years) in the 1995 National Junior weightlifting Championships and the 1996 Junior Olympics volunteered to complete a survey after they completed their respective competitions. The questionnaire included measures of goal perspectives, enjoyment, effort, perceived ability, and physical self-worth. Canonical correlations between goal perspectives (i.e., task and ego orientation) and the motivational responses revealed 2 significant functions: (a) A high task-low ego orientation was associated with high enjoyment, and (b) a high ego-low task orientation was associated with low effort, low physical self-worth, and high perceived ability. The results provide additional evidence to suggest that coaches and parents should attempt to foster task involvement among their young athletes so that the emphasis is on mastery, effort, and improvement rather than normative comparison.